Sociodemographic factors associated with job stress among secondary school teachers in Kelantan - Rasudin, Nur Syahmina; Shohaimi, Shamarina; Hassan, Siti Aishah; Zainuddin, Huda (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Job stress has been identified as one of the widespread problems among school teachers (Arikewuyo, 2004). Stress response that related to the workplace is known as a job stress. The aim of this study are to determine the prevalence of job stress among secondary school teachers in Kelantan, to identify the sociodemographic factors and medical history that related to job stress. This is a preliminary result of the study. This is a cross sectional study design with 680 respondents included in the study. The sociodemographic questionnaire (gender, race, marital status, level of education, age, years of teaching and household income), medical history (hypertension, asthma, diabetes and peptic ulcer) and Teacher Stress Level Inventory (TSLI) were administered to respondents. Data were analyzed for multiple regression analysis using Stata. TSLI had a good Cronbach Alpha >7.0. The prevalence of job stress among secondary school teachers in Kota Bharu was 40.3%. Age, gender, marital status and hypertension found to had significant prediction on job stress among school teachers in Kota Bharu, Kelantan (p-value <0.001). This preliminary analysis concluded that age, gender, marital status and hypertension are significant predictors for job stress.